An Intracellular Arrangement of Histoplasma capsulatum Yeast-Aggregates Generates Nuclear Damage to the Cultured Murine Alveolar Macrophages - Pitangui, Nayla de Souza; Sardi, Janaina de Cássia Orlandi; Voltan, Aline R.; dos Santos, Claudia T.; da Silva, Julhiany de Fátima; da Silva, Rosangela A. M.; Souza, Felipe O.; Soares, Christiane P.; Rodríguez-Arellanes, Gabriela; Taylor, Maria Lucia; Mendes-Giannini, Maria J. S.; Fusco-Almeida, Ana M. (Frontiers in Microbiology, 2016)
Histoplasma capsulatum is responsible for a human systemic mycosis that primarily affects lung tissue. Macrophages are the major effector cells in humans that respond to the fungus, and the development of respiratory disease depends on the ability of Histoplasma yeast cells to survive and replicate within alveolar macrophages. Therefore, the interaction between macrophages and H. capsulatum is a decisive step in the yeast dissemination into host tissues. Although the role played by components of cell-mediated immunity in the host's defense system and the mechanisms used by the pathogen to evade the host immune response are well understood, knowledge regarding the effects induced by H. capsulatum in host cells at the nuclear level is limited. According to the present findings, H. capsulatum yeast cells display a unique architectural arrangement during the intracellular infection of cultured murine alveolar macrophages, characterized as a formation of aggregates that seem to surround the host cell nucleus, resembling a "crown". This extranuclear organization of yeast-aggregates generates damage on the nucleus of the host cell, producing DNA fragmentation and inducing apoptosis, even though the yeast cells are not located inside the nucleus and do not trigger changes in nuclear proteins. The current study highlights a singular intracellular arrangement of H. capsulatum yeast near to the nucleus of infected murine alveolar macrophages that may contribute to the yeast’s persistence under intracellular conditions, since this fungal pathogen may display different strategies to prevent elimination by the host's phagocytic mechanisms.